The intercultural crafting of real Aboriginal country and manhood in Central Australia - Ottosson, Åse (The Australian journal of anthropology, 2012)
This article explores country music as an important means for Aboriginal men in Central Australia to articulate contemporary forms of manhood and indigeneity. These desert men perceive their own music scene as a last stronghold for real country music. The article demonstrates how such notions of real involve the ongoing intercultural mediation of global and local male aesthetic styles and manhood ideals. In making and performing their country music, desert men continue to draw on enduring ancestral regimes for male demeanour that resonate with global country music imagery and practice, as well as with prominent non-Indigenous models of manhood in the regional settler history.